Characteristic of Bacterias And Antibiotic Sensitivity of Blood Culture in Sepsis - Jesica Sidabutar; Nurmalia Purnama Sari; Phey Liana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Sepsis is a group of symptoms caused by infection, characterized by organ dysfunction due to compromised hosts response to infection hence may lead to a life-threatening condition. One of the treatments for sepsis stated in one hour-bundle is the administration of broad-spectrum antibiotics before the culture results obtained. Improper use of antibiotics may lead to antibiotic resistance. The purpose of this study was to describe the microbes pattern and their sensitivity to antibiotics in patients with sepsis at Muhammad Hoesin Hospital, Palembang, to contribute to a useful treatment guideline and to provide a reference for further research. Methods: This study was a descriptive observational study with a cross-sectional design using medical record of patients diagnosed with sepsis whose blood culture results were positive. This study was conducted at Muhammad Hoesin Hospital, Palembang, from January 2017 to December 2018. The data was processed and analyzed by univariate analysis using the SPSS 21.0 computer program. Results: The study subjects were predominantly children with Gram-positive bacteria (24.6%) as the most common cause. The most common bacteria observed were Staphylococcus epidermidis (35.7%), Staphylococcus aureus (27.3%), Staphylococcus haemolyticus (24%), and Staphylococcus hominis (21.4%). Linezolid (100%), nitrofurantoin (100%), and quinupristin/dalfopristin (100%) were found to be sensitive to gram-positive bacteria. Conclusion: Gram-positive bacteria were the most common cause of sepsis in Muhammad Hoesin Hospital, Palembang. The bacteria were sensitive to linezolid, nitrofurantoin, and quinupristin/ dalfopristin.